2012
DOI: 10.1002/jpln.201100237
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of N : P ratio and endogenous phytohormones during development of phosphorus toxicity in Brassica campestris spp. parachinensis

Abstract: Agricultural practices may lead to excessive phosphorus (P) accumulation in soil. The effects of excessive P on Chinese flowering cabbage (Brassica campestris spp. parachinensis) were investigated by exposing plants for 4 weeks in solution containing 1, 2, 3, 5, and 7 mM NaH2PO4. Phosphorus concentrations [P] greater than 3 mM produced significantly stunted growth, together with reduced appearance quality due to overaccumulation of anthocyanin in the epidermis of flower stalk. Nitrate concentrations in the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The lack of Fe nutrition gradually becomes the key factor limiting the yield of flowering Chinese cabbage due to the continuous increase in multiple cropping index and the increasing degree of soil alkalization. Our previous study indicated that mineral nutrition had clear effects on the growth, yield, quality, and disease resistance of flowering Chinese cabbage [11][12][13][14]. However, the effects of Fe deficiency on the growth and development of flowering Chinese cabbage and its related physiological characteristics are still lacking an investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of Fe nutrition gradually becomes the key factor limiting the yield of flowering Chinese cabbage due to the continuous increase in multiple cropping index and the increasing degree of soil alkalization. Our previous study indicated that mineral nutrition had clear effects on the growth, yield, quality, and disease resistance of flowering Chinese cabbage [11][12][13][14]. However, the effects of Fe deficiency on the growth and development of flowering Chinese cabbage and its related physiological characteristics are still lacking an investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of Fe nutrition gradually becomes the key factor limiting the yield of owering Chinese cabbage due to the continuous increase of multiple cropping index and the higher and higher degree of soil alkalization. Our previous study indicated that mineral nutrition has obvious effects on the growth, yield, quality, and disease resistance of owering Chinese cabbage (Chai et al 2013;Yang et al 2000Yang et al , 2004Yang et al , 2012.…”
Section: Introductionmentioning
confidence: 99%